Gold rush girl - Avi, 1937- (Candlewick Press, 2020)
In 1848 Providence, Rhode Island, Victoria "Tory" Blaisdell lives a boring life but dreams of being adventurous. When her father loses his job, he and her brother Jacob head to find their fortune in the California Gold Rush. However, Tory stows away on their ship and ends up caring for her brother when their father goes into the gold fields. Then Jacob disappears and Tory risks everything to find him.